Indoor air quality assessment in selected rural schools in Negeri Sembilan and its implications on children's healthNur Natasha Zafirah Binti Zainal Abidin - Zainal Abidin, Nur Natasha Zafirah (2023)
Indoor Air Quality (IAQ) is defined as the description of pollutant concentrations and temperature conditions that may have a negative impact on the health, comfort, and performance of facility occupants. The researcher measured the concentration of indoor air pollutants (CO, CO2, PM2.5, PM10 and bacteria); examined the effects of IAP on children's health; and investigated the relationship between concentration levels and the health impacts of IAP on children in selected rural schools in Negeri Sembilan. Quantitative research was conducted to fulfil the study's objectives. Quantitative data collected at two selected schools provided adequate information on concentration levels of IAPs and the health effects of IAPs on children (SKP4 and SKP5). Simple linear regression is used to examine the relationship between these variables. According to the findings, several indoor air pollutants exceeded the ICOP requirement for IAQ 2010, including temperature, relative humidity, and air movement. Furthermore, the children have reported symptoms such as drowsiness, irritation, stuffy nose, dizziness, headache, hoarseness, and dry throat. Moreover, some IAP variables at both schools had a significant association with presenting symptoms. Finally, IAQ assessments were successfully completed in the two selected rural schools in Negeri Sembilan, and the assessments met all the research objectives. Consider the fact that the IAQ may vary depending on the density of occupancy and activity at the sampling points. Thus, longterm IAQ monitoring programs and more frequent surveys of health symptoms are required to obtain more specific information on IAQ that is associated with health symptoms.